The influence of islamic capital market literacy toward intention to invest in islamic capital market: Does risk perception mediate the relationship? - Bastomi, Mohamad; Sudaryanti, Dwiyani (Journal of Accounting and Investment, 2024)
Research aims: This study was motivated by the limited study on the Islamic capital market, mainly in the behavioral finance field. Moreover, the incongruity findings in prior research investigations suggest additional exploration to elucidate the correlation between literacy and investing intention. This study, therefore, aims to clarify financial literacy roles in investment intention as mediated by risk perception. Specifically, the effect of Islamic capital market literacy on the intention to invest in the Islamic capital market was scrutinized.Design/Methodology/Approach: The present study employed quantitative methodology to address the issue under investigation. The study's sample was comprised of 200 respondents from the Generation Z investor population residing in Malang City. The research instrument used a set of seven Likert scales. The present study also utilized Partial Least Squares Structural Equation Modelling (PLS-SEM) for data analysis.Research findings: The research findings uncovered that Islamic capital market literacy affected risk perception and investment intention, and risk perception had a direct effect on investment intention. In addition, risk perception also successfully mediated the effect of capital market literacy on Gen Z's investment intention in the Islamic capital market.Theoretical contribution/Originality: This research has made a valuable contribution to the existing body of Islamic capital market literature, which has received limited attention. The research highlights the significance of Islamic capital literacy and establishes a favorable perspective of risk as a practical aspect. The results also have valuable input for the government in developing policies that promote increased involvement of young individuals in investing activities by enhancing literacy levels. Practitioner/Policy implication: The research highlights the significance of establishing a favourable perspective of risk as a practical aspect. The results of this study can be a helpful asset for governmental organisations seeking to develop policies that promote increased involvement of young individuals in investing activities by enhancing literacy levels. Research limitation/Implication: Nevertheless, one problem identified in this study is the lack of differentiation between respondents based on their level of literacy and the duration of their engagement. This aspect holds significant importance in influencing an individual's perception of risk.